Perbandingan Medan Pandang Teleskop dalam Pengamatan Konjungsi Bulan – Jupiter dari Kota Medan, Barus, dan Lhokseumawe - Hariyadi Putraga; Muhammad Dimas Firdaus; Marataon Ritonga; Arwin Juli Rakhmadi; Ruslandi Ruslandi; Ismail Ismail (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
Astronomical phenomenon occur for only a limited amount of time. Observing these phenomenon requires competent promoters and appropriate instruments. The field of view is one of the things that needs to be clearly known so that the observation can take place properly. In this study, joint observations were made between IAIN Lhokseumawe Falak Science Study Programme and OIF UMSU in Medan and Barus. The instruments used in these observations are different, resulting in a variety of fields of view and calculations are needed to get a description of the results. This study aims to calculate the field of view and visibility of the observed phenomenon, the conjunction of the Moon - Jupiter. The results obtained are for the instrument used by IAIN Lhokseumawe Falak Science Study Program at Malikussaleh Observatory has a field of view of 2°7'46.13‘ × 1°25'22.25’, the instrument used by UMSU Medan Falak Science Observatory has a field of view of 1°8'26.96‘ × 0°54'45.57’, and the instrument used by the OIF UMSU Barus team has a field of view of 1°0'43.74’ × 0°41'1.98. Using this combination of instruments cannot observe the conjunction phenomenon, because the elongation of the Moon - Jupiter at the time of the observation is >4°, so to be able to get the visibility of the phenomenon in 1 image requires an instrument that produces a field of view of 5°.